Bio‐Based Gradient Composites for 3D/4D Printing With Enhanced Mechanical, Shape Memory, and Flame‐Retardant Properties - Mohammadreza Lalegani Dezaki; Callum Branfoot; Jon Baxendale; Mahdi Bodaghi (Macromolecular Materials and Engineering)
Abstract This study explores the 3D/4D printing of polylactic acid (PLA) composites reinforced with natural particles from mussels PLA (MPLA) and wheat PLA (WPLA) using fused filament fabrication (FFF). The study employs functionally graded (FG) and multi‐material (MM) printing processes emphasizing biodegradable and bio‐derived materials. Shape memory polymer composites (SMPCs) with various MM and FG combinations are printed and examined. The microstructure, mechanical properties, flammability, and shape memory characteristics of these SMPCs are evaluated. The findings demonstrate that incorporating mussel and wheat particles enhances the mechanical performance of PLA, with a reduced burning rate compared to pure PLA samples. A sandwich FG composite structure shows superior strength in compression, tensile, and three‐point bending tests, with WMWFG samples exhibiting a 106% increase in tensile strength compared to WPLA samples. The shape recovery and fixity of the 4D‐printed SMPCs are investigated and WPLA specimens reveal the highest shape recovery ratio of ≈ 93.3% ± 1%. These findings highlight the potential of 4D‐printed SMPCs for diverse applications, spanning shape morphing, human‐material interaction, and mechanical engineering. Additionally, the research contributes to sustainability by promoting reduced material consumption and waste generation, as demonstrated by creating reusable and lightweight objects such as miniature pots, cutlery, holders, grippers, and wrappers.